Organizing to rule: structure, agent, and explaining presidential management styles in Africa. Issue 3 (3rd April 2018) - Ishiyama, John; Breuning, Marijke; Widmeier, Michael
ABSTRACT: Recent studies of comparative presidentialism have emphasized the importance of informal relationships between presidents and other political actors in explaining how presidents build governing coalitions. What has generally been under-investigated in the literature is how the characteristics of "presidents as agents" impact how they interact with other political actors – in particular, how presidents relate to their cabinets in terms of turnover and inclusiveness. We hypothesize that presidents who were former rebel leaders will behave very differently from presidents that do not have such backgrounds. To test our hypotheses, we collected data from 36 countries that are classified either as presidential or semi-presidential systems in Africa with 93 individual presidential administrations from 1990 to 2009. We found that presidents who were former rebel leaders were less likely to have major cabinet turnovers than other presidents. However, former rebel leaders did not have less politically inclusive cabinets (at least in partisan terms) but did have less ethnically inclusive cabinets than presidents with other backgrounds. The results suggest that agent characteristics, that is, the previous experiences of the president as a decision maker, are as important as the structural constraints he or she faces.